Researching eighteenth-century fraud in the Old Bailey: reflections on court records, archives, and digitisation - Griffiths, Cerian Charlotte (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
This article seeks to provide reflection and guidance to researchers of fraud in Britain during the eighteenth and nineteenth centuries. This reflection explains two reasons why there is a dearth of historical research into fraud offences. These reasons are ontological and methodological. The definitions and laws of fraud are complex and difficult to identify, and one of the most accessible court archive, the Old Bailey Sessions Papers (the Proceedings), needs to be treated with caution by the researcher of fraud. This article uses the in-depth historiography surrounding the Proceedings and applies this to the research of fraud offences which, this article argues, require a particular methodological approach.